Chapter Economic inequality in the rural Southern Low Countries during the Fifteenth century: sources, data and reflection - Lambrecht, Thijs (Datini Studies in Economic History, 2020)
This chapter seeks to explore local and regional variation in levels of inequality in different types of rural localities and regions within the late medieval County of Flanders. Our research indicates that fiscal sources for the County of Flanders can produce reliable data on the distribution of income during the late medieval period. The analysis of these data shows that important local and regional differences can be observed in the distribution of rural income. To a large extent, these local variations can be explained by differences in access to local economic resources. Our results, however, also indicate that substantial regional differences in access to rural resources can produce similar income distributions.